Simon Smith diary and account book - Smith, Simon, active 1863.
Diary kept by Smith, during his service in the 153rd Pennsylvania Infantry Regiment, describing troop movements in Pennsylvania, Maryland, and Virginia, and the Battle of Chancellorsville, Chancellorsville, Va. Smith also describes being wounded in battle, taken prisoner, and transported to Libby Prison, Richmond, Va. Diary and account book contain personal accounts, 1879-1914.
Union Army soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army. -- Pennsylvania Infantry Regiment, 153rd (1862-1863); Libby Prison; Chancellorsville, Battle of, Chancellorsville, Va., 1863.; Maryland -- History -- Civil War, 1861-1865.; Pennsylvania -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Virginia -- History -- Civil War, 1861-1865.; Soldiers